Pengaruh Kebiasaan Membaca Pada Perkembangan Kognitif Anak Slow Learner di Sekolah Inklusi - Annisa, Ridha; Fitra, Ringgi Rahmat; Wulandari, Zakiah Fitri (Universitas Negeri Gorontalo, 2025)
This research aims to examine the influence of reading habits on the cognitive development of slow learner children in inclusive schools. The Indonesian education system will continue to develop. In every school setting, reading is one of the most important language skills students must learn. Reading is a process of understanding various forms of language, such as letters and grammar as well as the ability to understand ideas. The research results show that reading habits must be started from the beginning, not only at school as a place to develop reading habits but also at home or in an environment that can provide positive things for students and can take advantage of learning books that can improve reading habits in the cognitive development of Slow Learner children in Inclusive Schools. This article also explores the role of an environment that supports reading habits and is recommended for parents, teachers and society to create a good literacy culture among children. In conclusion, from the results of literature study research, by implementing consistent reading habits and supported by the role of parents, the community and various teacher strategies, students will be able to increase their literacy, which has a direct impact on students' cognitive development.